Correlation of serum level of albumin with platelet count and platelet aggregation assessed by adenosine diphosphate agonist in children with nephrotic syndrome - Andar Laura Nainggolan; Sri Sudarwati; Dany Hilmanto (Paediatrica Indonesiana, 2019)
Background Nephrotic syndrome (NS) is the most common renal disease among children, and contributes to life-threatening complications such as thromboembolic disease. Platelets are considered to be important agents in thrombotic events among NS patients. The gold standard assessment for platelet aggregation is the use of adenosine diphosphate (ADP) agonist, however, it is expensive and not accessible in smaller health facilities. Thus, other thrombosis parameters are needed. Previous studies suggested that low albumin increased the risk of thrombosis in NS patients. Objective To assess for a possible correlation between albumin level and platelet count as well as platelet aggregation. Methods This cross-sectional study was conducted in children with nephrotic syndrome who were admitted to the Pediatric Nephrology Department in Dr. Hasan Sadikin General Hospital, Bandung, West Java, from November 2017 to March 2018. Subjects were selected by consecutive sampling. Serum albumin, platelet count, and platelet aggregation were measured. Statistical analysis was conducted by Spearman’s test. Results A total of 32 patients participated in the study, with mean age of 109 (SD 7.4) months. Most subjects were male (56%). Subjects’ mean serum albumin level was 2.06 (SD 1.23) g/dL; mean platelet count was 453,062.5 (SD 187,443.90)/mm3; and mean platelet aggregation values for ADP agonist concentrations of 10, 5, 2.5, and 1 mM were 86.8 (SD 8.63)%, 82.4 (SD 15.33)%, 66.6 (SD 24.90)%, 34.95 (SD 31.69)%, respectively. Partial correlation analysis revealed significant negative associations between albumin and platelet count as well as platelet aggregation assessed with 1 mM of ADP concentration (P<0.001), with Spearman correlation coefficients of -0.641 and -0.634, respectively. Conclusion Serum albumin level had a moderately negative correlation with platelet count and platelet aggregation value.